2018
DOI: 10.1002/ajmg.c.31607
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counseling globally: Where are we now?

Abstract: The genetic counseling profession is continuing to develop globally, with countries in various stages of development. In some, the profession has been in existence for decades and is increasingly recognized as an important provider of allied health, while in others it is just beginning. In this article, we describe the current global landscape of the genetic counseling specialty field's professional development. Using examples of the United States, United Kingdom, Canada, Australia, South Africa, and various c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
112
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 26 publications
(25 reference statements)
0
112
0
1
Order By: Relevance
“…To implement an independent genetic counseling profession in Mexico, thought must be put into what type of training would best suit the current infrastructure. Our study participants agree that the most appropriate way to train genetic counselors in Mexico would be to offer a 2‐year Masters training program, similar to the approach taken in the Philippines and other countries (e.g., Indonesia, Japan, Malaysia) (Ormond et al, ). Furthermore, they suggest the training program focus on individuals who have a background in a health‐related field.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…To implement an independent genetic counseling profession in Mexico, thought must be put into what type of training would best suit the current infrastructure. Our study participants agree that the most appropriate way to train genetic counselors in Mexico would be to offer a 2‐year Masters training program, similar to the approach taken in the Philippines and other countries (e.g., Indonesia, Japan, Malaysia) (Ormond et al, ). Furthermore, they suggest the training program focus on individuals who have a background in a health‐related field.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, they suggest the training program focus on individuals who have a background in a health‐related field. There is significant variation across different countries and training programs about whether genetic counseling trainees must have prior health‐related training and experience or are accepted with scientific bachelor's degrees (Ormond et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the field has grown in India and elsewhere since the course was conceived in the year 2016, there are still several challenges surrounding genetic counseling workforce development. These challenges, including relatively low awareness of the genetic counseling profession, limited opportunities for shadowing, lack of national recognition of genetic counseling as a healthcare service, and lack of establishment of practice standards, are not unique to India (Baty, 2018; Bucio, Ormond, Hernandez, Bustamante, & Lopez Pineda, 2019; Laurino et al, 2017; Ormond et al, 2018; Sun, Liang, Zhu, Shen, & He, 2019). Country‐specific studies to assess the factors that influence workforce development could be beneficial in providing a framework for growth of the profession.…”
Section: Discussionmentioning
confidence: 99%
“…Later, additional publications also described the importance of diversifying the population of GCs (Lega, Veach, Ward, & LeRoy, ; Schoonveld, Veach, & LeRoy, ), and in 2011, an entire issue of the JOGC was dedicated to GCs’ cultural competency. More recently, Ormond et al () described the availability of genetic counseling globally and highlighted the challenge of this service being offered in different languages. Despite these efforts, data from the 2018 National Society of Genetic Counselors (NSGC) Professional Status Survey showed that only 14% of respondents (364/2,543) provide genetic counseling in a language other than English, including Spanish (169/364) and French (44/364) (NSGC, ).…”
Section: Process For Adding a New Language To Lexigene®mentioning
confidence: 99%
“…Later, additional publications also described the importance of diversifying the population of GCs (Lega, Veach, Ward, & LeRoy, 2005;Schoonveld, Veach, & LeRoy, 2007), and in 2011, an entire issue of the JOGC was dedicated to GCs' cultural competency. More recently, Ormond et al (2018) described the availability of genetic counseling globally and highlighted the challenge of this service being offered in different languages. Despite these efforts, data from the 2018…”
mentioning
confidence: 99%